An Exploration of Teacher Sense-Making Around Whiteness During a Critical Professional Development Course - Jami Carmichael; Carlos R. Casanova; Justine Parnell; Jordan King; Molly Cashion; Robert McGehee (AERA Open)
There is a dearth in research on how practicing teachers understand and grapple with whiteness during critical professional development (CPD). To address this, we explored P-12 educators’ sense-making around whiteness as they learned about the theories that underpin Youth Participatory Action Research (YPAR) during CPD. Utilizing a critical whiteness studies lens, we found that educators recognized the connection between systemic racism and student harm, and both named and avoided naming whiteness as they navigated its influence. Our findings highlight the complexities of how educators engage with whiteness during CPD, revealing both an awareness of systemic racism and its consequences and the challenge of explicitly naming whiteness. We underscore the need for CPD to help educators interrogate and name whiteness, without centering it, and to build teacher capacity to support students of Color. Future research should explore how CPD can sustain these efforts and support educators in developing actionable anti-racist practices.